Positive electrode material and preparation method thereof, positive plate and sodium ion battery
By doping Ca/Sr elements into the positive electrode material of sodium ion battery and setting a B-element cladding layer, the morphology and cyclic performance of the positive electrode material after sintering is solved, and the battery capacity and rate performance are improved.
Patent Information
- Application Number
- CN202411298546.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-20
AI Technical Summary
The positive electrode materials of existing sodium ion batteries have problems such as poor morphology, poor processing performance, low compaction density, prone to gel phenomena, low battery capacity and poor circulation after sintering.
Improve the single crystal morphology of the carbonate precursor by doping Ca elements and/or Sr elements, and a cladding layer containing B elements is provided on the surface of the matrix material to improve the compaction density and cyclic performance of the material and reduce the sub-parameters Reaction and slurry gel phenomenon.
The particle round single crystal morphology of the positive electrode material is achieved, the compaction density and rate performance are improved, the battery capacity and circulation performance are improved, and the problems of poor morphology, poor processing performance and poor circulation are solved.
Smart Images

Figure CN119170767A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet and a sodium ion battery. Background Art
[0002] The main advantages of sodium-ion batteries over lithium-ion batteries include cost advantages, resource abundance, higher safety, better stability, and fast charging capability.
[0003] The low-copper carbonate co-precipitation precursor of the layered oxide positive electrode of the sodium ion battery is cheaper than the hydroxide co-precipitation precursor. However, the carbonate precursor has the problems of poor morphology of the finished positive electrode material after sintering, poor processing performance, low compaction density, easy gelation, low battery capacity, and poor cycle.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The first purpose of the present invention is to provide a positive electrode material. By doping Ca elements and / or Sr elements to assist melting, the single crystal morphology of the positive electrode material sintered from a carbonate precursor can be effectively improved, and a single crystal morphology with rounded particles can be obtained. Sr / Ca enters the sodium layer to stabilize the structure, thereby increasing the compaction density of the material, and improving the rate performance and capacity. At the same time, by providing a dense B-containing coating layer, the specific surface area of the positive electrode material can be reduced, the occurrence of side reactions can be reduced, the cycle performance can be improved, the air stability of the material can be improved, and the slurry gel phenomenon can be reduced.
[0006] The second object of the present invention is to provide a method for preparing a positive electrode material, wherein the single crystal morphology of the positive electrode material prepared by the method is good, the processing performance is good, the compaction density is high, and the gel phenomenon is not easy to occur. The battery capacity and rate are high and the cycle performance is good. The problem of poor morphology, poor processing performance, low compaction density, easy gel phenomenon, low battery capacity and poor cycle in the finished positive electrode material after sintering the low-copper carbonate precursor in the prior art is solved.
[0007] The third object of the present invention is to provide a positive electrode sheet with high capacity and rate and good cycle performance.
[0008] A fourth object of the present invention is to provide a sodium ion battery having the advantages of high capacity, good rate performance, and excellent cycle performance.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] The present invention first provides a positive electrode material, comprising a base material and a coating layer coated on the surface of the base material.
[0011] The chemical formula of the matrix material is Na x A y Ni a Cu b Fe c Mn d O2, wherein 0.98≤x≤1.02, 0.001≤y≤0.02, 0.29≤a≤0.31, 0.02≤b≤0.04, 0.31≤c≤0.36, 0.32≤d≤0.36, and A includes Ca element and / or Sr element.
[0012] The coating layer contains B element, and the ratio of the mass of the B element to the mass of the base material is 0.005-0.01:1.
[0013] Furthermore, the particle size D of the positive electrode material 50 4~20μm.
[0014] Furthermore, the specific surface area of the positive electrode material is ≤0.5m 2 / g.
[0015] Furthermore, the compaction density of the positive electrode material is ≥3.0 g / cm 3 .
[0016] The present invention further provides a method for preparing the positive electrode material, comprising the following steps:
[0017] A copper-nickel-iron-manganese carbonate precursor, a sodium source and an A-containing dopant are mixed and sintered to obtain a matrix material; the A element in the A-containing dopant includes at least one of Ca and Sr, and the ratio y of the molar amount of the A element to the molar amount of the copper-nickel-iron-manganese carbonate precursor is 0.001 to 0.02.
[0018] The base material and the B-containing coating agent are mixed and then calcined to obtain the positive electrode material; the ratio z of the mass of the B element in the B-containing coating agent to the mass of the base material is 0.005-0.01.
[0019] Furthermore, the sum of the theoretical carbon content and the theoretical sulfur content in the positive electrode material is satisfy: in, The unit is ppm, ±200 is the error coefficient; S is the specific surface area of the positive electrode material, D 50 is the particle size D of the positive electrode material 50 .
[0020] Furthermore, the
[0021] Furthermore, the chemical formula of the nickel iron manganese carbonate precursor is Ni m Cu n Fe p Mn q CO3, wherein 0.29≤m≤0.31, 0.02≤n≤0.04, 0.31≤p≤0.36, 0.32≤q≤0.36, and m+n+p+q=1.
[0022] Furthermore, the sodium source includes at least one of sodium carbonate, sodium hydroxide and sodium bicarbonate.
[0023] Furthermore, the A-containing dopant includes at least one of metal oxides, carbonates and hydroxides containing the A element.
[0024] Furthermore, the B-containing coating agent includes boric acid and / or boron oxide.
[0025] Furthermore, the sintering temperature is 900-1000° C., and the holding time is 10-30 hours.
[0026] Furthermore, the sintering atmosphere includes air atmosphere and / or oxygen atmosphere.
[0027] Furthermore, the calcination temperature is 300-800° C., and the holding time is 5-15 hours.
[0028] Furthermore, the calcination atmosphere includes air atmosphere and / or oxygen atmosphere.
[0029] The present invention further provides a positive electrode sheet, comprising the positive electrode material, or the positive electrode material prepared by the preparation method of the positive electrode material.
[0030] The present invention also provides a sodium ion battery, comprising the positive electrode sheet.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The positive electrode material provided by the present invention can effectively improve the single crystal morphology of the positive electrode material sintered from the carbonate precursor by doping with Ca and / or Sr elements to form a single crystal morphology with rounded particles, and Sr / Ca enters the sodium layer to stabilize the structure, thereby improving the compaction density of the positive electrode material, and at the same time, improving the rate performance and capacity. At the same time, by providing a coating layer containing B elements, the specific surface area of the positive electrode material can be reduced, the generation of side reactions can be reduced, and the cycle performance can be improved; at the same time, the air stability of the material can be improved, and the slurry gel phenomenon can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 This is a scanning electron microscope image of the positive electrode material prepared in Example 1 provided by the present invention;
[0035] Figure 2 This is a scanning electron microscope image of the positive electrode material prepared in Comparative Example 1 provided by the present invention. DETAILED DESCRIPTION
[0036] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0037] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0038] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0039] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.
[0040] The present invention first provides a positive electrode material, specifically a layered oxide positive electrode material, which comprises a base material and a coating layer coated on the surface of the base material.
[0041] Wherein, the chemical formula of the matrix material is Na x A y Ni a Cu b Fe c Mn d O2. Wherein, 0.98≤x≤1.02, 0.001≤y≤0.02, 0.29≤a≤0.31, 0.02≤b≤0.04, 0.31≤c≤0.36, 0.32≤d≤0.36, and A includes Ca element and / or Sr element. Wherein, x includes but is not limited to any point value of 0.98, 0.99, 1, 1.01, 1.02 or any range value between two of them; y includes but is not limited to any point value of 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.008, 0.01, 0.012, 0.014, 0.015, 0.016, 0.018, 0.02 or any range value between two of them; a includes but is not limited to any point value of 0.29, 0.30, 0.31 or any range value between two of them b includes but is not limited to any one of 0.02, 0.023, 0.025, 0.028, 0.03, 0.032, 0.035, 0.037, 0.04 or a range between any two of them; c includes but is not limited to any one of 0.31, 0.32, 0.33, 0.34, 0.35, 0.36 or a range between any two of them; d includes but is not limited to any one of 0.32, 0.33, 0.34, 0.35, 0.36 or a range between any two of them.
[0042] The coating layer contains element B, and the ratio of the mass of the element B to the mass of the matrix material is 0.005 to 0.01:1, including but not limited to any one of 0.005:1, 0.006:1, 0.007:1, 0.008:1, 0.009:1, and 0.01:1 or a range between any two of them.
[0043] The present invention can effectively improve the single crystal morphology of the positive electrode material sintered from the carbonate precursor by doping with Ca element and / or Sr element to assist melting, forming a single crystal morphology with rounded particles, and Sr / Ca enters the sodium layer to stabilize the structure, thereby improving the compaction density of the positive electrode material, and at the same time can also improve the rate performance and capacity.
[0044] Furthermore, the present invention provides a coating layer containing the B element, which can reduce the specific surface area of the positive electrode material, reduce the occurrence of side reactions, and improve the cycle performance; at the same time, it improves the air stability of the material and reduces the slurry gel phenomenon.
[0045] In some specific embodiments, the matrix material is made from a low-copper carbonate precursor, and the molar amount of copper in the low-copper carbonate precursor accounts for 0.02 to 0.04 of the sum of the molar amounts of nickel, iron, manganese and copper. The present invention solves the problems of poor morphology, poor processing performance, low compaction density, easy gelation, low battery capacity and poor cycle in the finished positive electrode material after sintering the low-copper carbonate precursor in the prior art.
[0046] In some specific embodiments, the particle size D of the positive electrode material is 50 4 to 20 μm; including but not limited to any point value of 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 10 μm, 12 μm, 13 μm, 15 μm, 18 μm, 20 μm or any range value between two of them. The particle size of the positive electrode material provided by the present invention is suitable.
[0047] In some specific embodiments, the specific surface area of the positive electrode material is ≤0.5 m 2 / g; but not limited to 0.5m 2 / g, 0.45m 2 / g, 0.4m 2 / g, 0.38m 2 / g, 0.35m 2 / g, 0.33m 2 / g, 0.31m 2 / g, 0.3m 2 / g, 0.28m 2 / g, 0.25m 2 / g or any range between them. Preferably less than 0.4 m 2 / g. The positive electrode material provided by the present invention has a small specific surface area.
[0048] In some specific embodiments, the compaction density of the positive electrode material is ≥3.0 g / cm 3 , including but not limited to 3.0g / cm 3 、3.1g / cm 3 、3.2g / cm 3 , 3.3g / cm 3 、3.4g / cm 3 , 3.5g / cm 3 The positive electrode material provided by the present invention has a high compaction density.
[0049] The present invention further provides a method for preparing the positive electrode material, comprising the following steps:
[0050] A copper-nickel-iron-manganese carbonate precursor, a sodium source and an A-containing dopant are mixed and sintered, and then pulverized after cooling to obtain a matrix material. The A element in the A-containing dopant includes at least one of Ca and Sr, and the molar amount of the A element accounts for the molar amount of the copper-nickel-iron-manganese carbonate precursor. The ratio y is 0.001 to 0.02, and y includes but is not limited to any point value of 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.008, 0.01, 0.012, 0.014, 0.015, 0.016, 0.018, 0.02 or a range value between any two of them.
[0051] The base material and the B-containing coating agent are mixed and calcined, and then pulverized after cooling to obtain the positive electrode material. The ratio z of the mass of the B element in the B-containing coating agent to the mass of the base material is 0.005 to 0.01, wherein z includes but is not limited to any one of 0.005, 0.006, 0.007, 0.008, 0.009, and 0.01 or a range between any two of them.
[0052] The present invention can effectively improve the single crystal morphology of the positive electrode material sintered from the carbonate precursor by doping with Ca element and / or Sr element to assist melting, forming a single crystal morphology with rounded particles, and Sr / Ca enters the sodium layer to stabilize the structure, thereby improving the compaction density of the positive electrode material, and at the same time can also improve the rate performance and capacity.
[0053] Further coating B to form a dense coating layer can reduce the specific surface area of the positive electrode material, reduce the occurrence of side reactions, and improve the cycle performance; at the same time, it improves the air stability of the positive electrode material and reduces the slurry gel phenomenon.
[0054] The present invention solves the problems of poor morphology, poor processing performance, low compaction density, easy gelation, low battery capacity and poor cycle in the finished positive electrode material after sintering the low-copper carbonate precursor in the prior art.
[0055] In some specific embodiments, the ratio of the molar amount of the A element in the A-containing dopant to the molar amount of the copper-nickel-iron-manganese carbonate precursor is set to M A The ratio of the mass of the B element in the B-containing coating agent to the mass of the copper-nickel-iron-manganese carbonate precursor is set as m B , then m B / M A =0.3~5.
[0056] In some specific embodiments, the sum of the theoretical carbon content and the theoretical sulfur content in the positive electrode material is Satisfies the following relationship:
[0057] in, The unit is ppm, ±200 is the error coefficient; S is the specific surface area of the positive electrode material, D 50 is the particle size D of the positive electrode material 50 EXP(y) represents the natural exponential function, that is, the exponential function with the real number e (e≈2.71828) as the base, and its expression is EXP(y)=e y In the relationship, y is the ratio of the molar amount of the A element to the molar amount of the copper-nickel-iron-manganese carbonate precursor, which is also the chemical formula of the matrix material Na x A y Ni a Cu b Fe c Mn d The subscript value of the A element in O2. z is the ratio of the mass of the B element in the B-containing coating agent to the mass of the copper-nickel-iron-manganese carbonate precursor.
[0058] In some specific embodiments, the Including but not limited to any one of 600 ppm, 700 ppm, 800 ppm, 1000 ppm, 1200 ppm, 1500 ppm, 1800 ppm or a range between any two of them.
[0059] In some specific embodiments, the sum of the theoretical carbon content and the theoretical sulfur content in the positive electrode material is The difference between the actual (measured) carbon content and the actual (measured) sulfur content in the positive electrode material is ≤ 200 ppm, preferably 0. That is, the above relationship The sum of the actual carbon content and the actual sulfur content in the positive electrode material can be more accurately characterized.
[0060] In some specific embodiments, the chemical formula of the nickel iron manganese carbonate precursor is Ni m Cu n Fe p Mn qCO3, wherein 0.29≤m≤0.31, 0.02≤n≤0.04, 0.31≤p≤0.36, 0.32≤q≤0.36, and m+n+p+q=1. The nickel-iron-manganese carbonate precursor is a low-copper carbonate precursor. Among them, m includes but is not limited to any one of the point values of 0.29, 0.30, and 0.31, or a range of values between any two of them; n includes but is not limited to any one of the point values of 0.02, 0.023, 0.025, 0.028, 0.03, 0.032, 0.035, 0.037, and 0.04, or a range of values between any two of them; p includes but is not limited to any one of the point values of 0.31, 0.32, 0.33, 0.34, 0.35, and 0.36, or a range of values between any two of them; q includes but is not limited to any one of the point values of 0.32, 0.33, 0.34, 0.35, and 0.36, or a range of values between any two of them.
[0061] In some specific embodiments, the particle size D of the nickel iron manganese carbonate precursor is 50 Satisfy 3μm≤D 50 ≤9μm, including but not limited to any point value of 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm or a range value between any two of them.
[0062] In some specific embodiments, the specific surface area of the nickel iron manganese carbonate precursor satisfies BET of 10m 2 / g<BET<30m 2 / g, including but not limited to 12m 2 / g, 15m 2 / g, 18m 2 / g, 20m 2 / g, 23m 2 / g, 25m 2 / g, 28m 2 / g, or a range of values between them.
[0063] In some specific embodiments, the contents of impurity elements such as Na, S, Ca, Mg, Al, Zn, Co, Li, etc. in the nickel-iron-manganese carbonate precursor are each independently less than 5000 ppm.
[0064] In some specific embodiments, the sodium source includes at least one of sodium carbonate, sodium hydroxide and sodium bicarbonate, and two or three of them may also be selected.
[0065] In some specific embodiments, the A-containing dopant includes at least one of metal oxides, carbonates and hydroxides containing the A element, such as calcium oxide, calcium carbonate, strontium oxide, and the like.
[0066] In some specific embodiments, the B-containing coating agent includes boric acid and / or boron oxide.
[0067] In some specific embodiments, the sintering temperature is 900-1000°C, including but not limited to any point value of 900°C, 920°C, 940°C, 950°C, 980°C, 1000°C or a range between any two of them.
[0068] In some specific embodiments, the sintering holding time is 10 to 30 hours, including but not limited to any point value of 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, 22 hours, 24 hours, 26 hours, and 30 hours, or a range value between any two of them.
[0069] In some specific embodiments, the sintering heating rate is 1 to 10°C / min, including but not limited to any point value of 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, and 10°C / min, or a range value between any two of them.
[0070] In some specific embodiments, the sintering atmosphere includes air atmosphere and / or oxygen atmosphere.
[0071] In some specific embodiments, the calcination temperature of 300-800°C includes but is not limited to any point value of 300°C, 350°C, 400°C, 450°C, 500°C, 600°C, 700°C, 800°C or a range value between any two of them.
[0072] In some specific embodiments, the calcination holding time is 5 to 15 hours, including but not limited to any one of 5 hours, 6 hours, 8 hours, 10 hours, 12 hours, and 15 hours, or a range between any two of them.
[0073] In some specific embodiments, the heating rate of calcination is 1 to 10°C / min, including but not limited to any one of 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, and 10°C / min, or a range between any two of them.
[0074] In some specific embodiments, the calcination atmosphere includes air atmosphere and / or oxygen atmosphere.
[0075] The sintering and calcining adopts the above temperature and time, which is conducive to ensuring the sum of the theoretical carbon content and the theoretical sulfur content in the positive electrode material.
[0076] The present invention further provides a positive electrode sheet, comprising the positive electrode material, or the positive electrode material prepared according to the preparation method of the positive electrode material.
[0077] The positive electrode sheet has high capacity and rate and good cycle performance.
[0078] Optionally, the positive electrode sheet further includes a binder and a conductive agent, which is not limited in the present invention.
[0079] The present invention also provides a sodium ion battery, comprising the positive electrode sheet.
[0080] The sodium ion battery has the advantages of high capacity, good rate performance, and excellent cycle performance.
[0081] Optionally, the sodium ion battery further includes a negative electrode sheet, a separator and an electrolyte, which is not limited in the present invention.
[0082] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0083] Example 1
[0084] The method for preparing the positive electrode material provided in this embodiment comprises the following steps:
[0085] (1) Weigh a certain amount of copper-nickel-iron-manganese carbonate precursor Ni 0.29 Cu 0.04 Fe 0.31 Mn 0.36 CO3, weigh the corresponding sodium carbonate according to the molar ratio of sodium element to copper-nickel-iron-manganese carbonate precursor = 0.98, and weigh the corresponding calcium carbonate dopant according to the molar ratio of Ca element to copper-nickel-iron-manganese carbonate precursor y = 0.001. Mix the weighed raw materials in a high-speed mixer for 15 minutes until there are no obvious white spots to obtain a black-gray mixed material. Put the black-gray mixed material into an atmosphere furnace, introduce compressed air, sinter at 970°C and keep warm for 15 hours, then cool naturally to room temperature, take out the material and crush it to obtain the matrix material Na 0.9 8Ca 0.001 Ni 0.29 Cu 0.04 Fe 0.31 Mn 0.36 O2.
[0086] (2) According to the mass ratio of B element to matrix material z=0.005, the corresponding boric acid coating agent is weighed, the boric acid and matrix material are evenly mixed, and then calcined at 300°C for 10h in a compressed air atmosphere, and then crushed after cooling to room temperature to obtain the positive electrode material Na 0.98 Ca 0.001 Ni 0.29 Cu 0.04 Fe 0.31 Mn 0.36 O2@0.005B.
[0087] The positive electrode material prepared in this embodiment includes a base material and a coating layer coated on the surface of the base material. The chemical formula of the base material is Na 0.98 Ca 0.001 Ni 0.29 Cu 0.04 Fe 0.31 Mn 0.36 O2, the coating layer is boron oxide.
[0088] Example 2
[0089] The method for preparing the positive electrode material provided in this embodiment comprises the following steps:
[0090] (1) Weigh a certain amount of copper-nickel-iron-manganese carbonate precursor Ni 0.30 Cu 0.03 Fe 0.33 Mn 0.34 CO3, weigh the corresponding sodium carbonate according to the molar ratio of sodium element to copper-nickel-iron-manganese carbonate precursor = 1, and weigh the corresponding strontium carbonate dopant according to the molar ratio of Sr element to copper-nickel-iron-manganese carbonate precursor y = 0.001. Mix the weighed raw materials in a high-speed mixer for 15 minutes until there are no obvious white spots to obtain a black-gray mixed material. Put the black-gray mixed material into an atmosphere furnace, introduce compressed air, sinter at 980°C and keep warm for 15 hours, then cool naturally to room temperature, take out the material and crush it to obtain the matrix material NaSr 0.001 Ni 0.30 Cu 0.03 Fe 0.33 Mn 0.34 O2.
[0091] (2) According to the mass ratio of B element to matrix material z=0.005, the corresponding boron oxide coating agent is weighed, the boron oxide and the matrix material are evenly mixed, and then calcined at 500°C for 8h in a compressed air atmosphere, and then crushed after cooling to room temperature to obtain the positive electrode material NaSr 0.001 Ni 0.30 Cu 0.03 Fe 0.33 Mn 0.34 O2@0.005B.
[0092] The positive electrode material prepared in this embodiment includes a base material and a coating layer coated on the surface of the base material. The chemical formula of the base material is NaSr 0.001 Ni 0.30 Cu 0.03 Fe 0.33 Mn 0.34 O2, the coating layer is boron oxide.
[0093] Example 3
[0094] The preparation method of the positive electrode material provided in this embodiment is basically the same as that in Embodiment 2, except that, in step (1), the corresponding strontium carbonate dopant is weighed according to the molar ratio of Sr element to copper-nickel-iron-manganese carbonate precursor y=0.01.
[0095] Example 4
[0096] The preparation method of the positive electrode material provided in this embodiment is basically the same as that in Embodiment 2, except that, in step (1), the corresponding strontium carbonate dopant is weighed according to the molar ratio of Sr element to copper-nickel-iron-manganese carbonate precursor y=0.015.
[0097] Example 5
[0098] The method for preparing the positive electrode material provided in this embodiment comprises the following steps:
[0099] (1) Weigh a certain amount of copper-nickel-iron-manganese carbonate precursor Ni 0.31 Cu 0.02 Fe 0.35 Mn 0.32 CO3, weigh the corresponding sodium carbonate according to the molar ratio of sodium element to copper-nickel-iron-manganese carbonate precursor = 1.01, and weigh the corresponding calcium carbonate according to the molar ratio of Ca element to copper-nickel-iron-manganese carbonate precursor y = 0.01, and weigh the corresponding strontium carbonate according to the molar ratio of Sr element to copper-nickel-iron-manganese carbonate precursor y = 0.01. Mix the weighed raw materials in a high-speed mixer for 15 minutes until there are no obvious white spots to obtain a black-gray mixed material. Put the black-gray mixed material into an atmosphere furnace, pass compressed air, sinter at 960°C and keep warm for 15 hours, then cool naturally to room temperature, take out the material and crush it to obtain the matrix material Na 1.01 Sr 0.01 Ca 0.01 Ni 0.31 Cu 0.02 Fe 0.35 Mn 0.32 O2.
[0100] (2) According to the mass ratio of B element to matrix material z=0.008, the corresponding boron oxide coating agent is weighed, the boron oxide and the matrix material are evenly mixed, and then calcined at 800°C for 5h in a compressed air atmosphere, and then crushed after cooling to room temperature to obtain the positive electrode material Na 1.01 Sr 0.01 Ca 0.01 Ni 0.31 Cu 0.02 Fe 0.35 Mn 0.32 O2@0.008B.
[0101] The positive electrode material prepared in this embodiment includes a base material and a coating layer coated on the surface of the base material. The chemical formula of the base material is Na 1.01 Sr 0.01 Ca 0.01 Ni 0.31 Cu 0.02 Fe 0.35 Mn 0.32 O2, the coating layer is boron oxide.
[0102] Example 6
[0103] The method for preparing the positive electrode material provided in this embodiment comprises the following steps:
[0104] (1) Weigh a certain amount of copper-nickel-iron-manganese carbonate precursor Ni 0.30 Cu 0.03 Fe 0.33 Mn 0.34 CO3, weigh the corresponding sodium carbonate according to the molar ratio of sodium element to copper-nickel-iron-manganese carbonate precursor = 1.02, and weigh the corresponding calcium carbonate dopant according to the molar ratio of Ca element to copper-nickel-iron-manganese carbonate precursor y = 0.005. Mix the weighed raw materials in a high-speed mixer for 15 minutes until there are no obvious white spots to obtain a black-gray mixed material. Put the black-gray mixed material into an atmosphere furnace, introduce compressed air, sinter at 980°C and keep warm for 15 hours, then cool naturally to room temperature, take out the material and crush it to obtain the matrix material Na 1.0 2Ca 0.005 Ni 0.30 Cu 0.03 Fe 0.33 Mn 0.34 O2.
[0105] (2) According to the mass ratio of B element to matrix material z=0.005, the corresponding boric acid coating agent is weighed, the boric acid and matrix material are evenly mixed, and then calcined at 500°C for 8h in a compressed air atmosphere, and then crushed after cooling to room temperature to obtain the positive electrode material Na 1.02 Ca 0.005 Ni 0.30 Cu0.03 Fe 0.33 Mn 0.34 O2@0.005B.
[0106] The positive electrode material prepared in this embodiment includes a base material and a coating layer coated on the surface of the base material. The chemical formula of the base material is Na 1.02 Ca 0.005 Ni 0.30 Cu 0.03 Fe 0.33 Mn 0.34 O2, the coating layer is boron oxide.
[0107] Example 7
[0108] The preparation method of the positive electrode material provided in this embodiment is basically the same as that of Embodiment 6, except that, in step (2), the corresponding boric acid is weighed according to the mass ratio of B element to matrix material z=0.008.
[0109] Example 8
[0110] The preparation method of the positive electrode material provided in this embodiment is basically the same as that of Example 6, except that in step (2), the corresponding boric acid is weighed according to the mass ratio of B element to matrix material z=0.01.
[0111] Comparative Example 1
[0112] The preparation method of the positive electrode material provided in this comparative example is basically the same as that of Example 1, except that no calcium carbonate dopant and boric acid coating agent are added.
[0113] Comparative Example 2
[0114] The preparation method of the positive electrode material provided in this comparative example is basically the same as that of Example 7, except that no calcium carbonate dopant is added.
[0115] Comparative Example 3
[0116] The preparation method of the positive electrode material provided in this comparative example is basically the same as that of Example 6, except that no boric acid coating agent is added.
[0117] Comparative Example 4
[0118] The preparation method of the positive electrode material provided in this comparative example is basically the same as that of Example 6, except that in step (2), the corresponding boric acid is weighed according to the mass ratio of B element to matrix material z=0.02.
[0119] Comparative Example 5
[0120] The preparation method of the positive electrode material provided in this comparative example is basically the same as that of Example 6, except that in step (2), the calcination time is 2 hours.
[0121] Comparative Example 6
[0122] The preparation method of the positive electrode material provided in this comparative example is basically the same as that of Example 2, except that in step (1), the corresponding strontium carbonate dopant is weighed according to the molar ratio of Sr element to copper-nickel-iron-manganese carbonate precursor y=0.1.
[0123] The morphology and particle size of the positive electrode materials obtained in each embodiment and each comparative example 50 The test results of the specific surface area S, compacted density, and the carbon content (measured) and sulfur content (measured) are shown in Table 1. The sum of the theoretical carbon content and the theoretical sulfur content in the positive electrode material The calculation results are shown in Table 1, where y is the ratio of the molar amount of element A in the dopant containing A to the molar amount of the copper-nickel-iron-manganese carbonate precursor, z is the ratio of the mass of element B in the coating agent B to the mass of the copper-nickel-iron-manganese carbonate precursor, S is the specific surface area of the positive electrode material, D 50 is the median particle size D of the positive electrode material 50 .
[0124] Among them, the morphology test used a Hitachi S-4800 field emission scanning electron microscope with an acceleration voltage of 5kV, a magnification of 5k, and a shooting mode of SE.
[0125] The specific surface area test was conducted using a precision Gaobo specific surface area analyzer with reference to GB / T19587-2017 "Determination of the specific surface area of solid substances by gas adsorption BET method". The specific surface area of the material was tested using a precision Gaobo JW-DX dynamic adsorption specific surface area analyzer. 1g of sample was weighed, the heating temperature was set to 150°C, the degassing time was set to 60min, and the specific surface area data output after calculation by the software was recorded.
[0126] Table 1 Physical and chemical indicators of various positive electrode materials
[0127]
[0128]
[0129] Furthermore, the positive electrode materials prepared in each embodiment and each comparative example were used as active materials to prepare button batteries according to the following method: the active material, the conductive agent Super P, and the adhesive PVDF were used in a mass ratio of 90:5:5 to prepare the positive electrode material slurry using a degassing machine, and the solid content of the slurry was adjusted to 39% by using N-methylpyrrolidone (NMP). The adjusted slurry was coated on an aluminum foil using an automatic coating machine, and then dried at 120°C in a vacuum drying oven, rolled on a roller press, and punched on a slicer. After that, button 2032 batteries were assembled in a glove box. The electrolyte was 1.2 mol / L NaPF6, wherein the solvent was EC:PC:EMC=1:1:1 (volume ratio), and 2 wt.% of FEC was added. The diaphragm was a glass fiber diaphragm, and a metal sodium sheet was used as the counter electrode.
[0130] Then, electrochemical tests were performed: each button half-cell was charged and discharged on a Xinwei tester in the voltage range of 2.5 to 4.05V. 0.1C charge and discharge were performed three times, and then 1C charge and discharge tests were performed to test the 0.1C first discharge gram capacity, 1C first discharge gram capacity, and capacity retention rate after 50 cycles at 1C. The results are shown in Table 2.
[0131] The viscosity of the initial slurry and the slurry after 10 hours was tested using a viscosity tester. The viscosity change rate = (slurry viscosity after 10 hours - initial slurry viscosity) / initial slurry viscosity × 100%. The results are shown in Table 2.
[0132] Table 2 Electrochemical performance test results
[0133]
[0134]
[0135] In combination with Table 1 and Table 2, by comparing the embodiments with Comparative Example 1, it is shown that the doping and coating scheme provided by the present invention is effective, the positive electrode material provided by the present invention has good single crystal morphology, good processing performance, high compaction density, and is not prone to gel phenomenon. The battery prepared using the same has high capacity and rate, and good cycle performance.
[0136] Comparison of Example 7 with Comparative Example 2 shows that coating alone without doping cannot improve the strength of the material, resulting in low compaction.
[0137] Comparison of Example 6 with Comparative Example 3 shows that doping without coating alone cannot significantly improve the air stability of the material, and gelation will still occur.
[0138] Comparison of Example 6 with Comparative Example 4 shows that excessive coating will obviously lead to a decrease in material performance.
[0139] By comparing Example 6 with Comparative Example 5, it is shown that in Comparative Example 5, the coating time is short and the coating is incomplete, resulting in a significant decrease in the cycle performance.
[0140] By comparing Example 2 with Comparative Example 6, it is shown that the doping amount in Comparative Example 6 is too high, resulting in low capacity and poor cycle.
[0141] In addition, the SEM image of the positive electrode material prepared in Example 1 is shown in Figure 1 As shown, it can be seen that the positive electrode material is a single crystal morphology with round particles.
[0142] The SEM image of the positive electrode material prepared in Comparative Example 1 is shown in Figure 2 As shown, it can be seen that the particles of the positive electrode material have poor sphericity and a single crystal morphology.
[0143] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A positive electrode material, It is characterized in that It comprises a base material and a coating layer coated on the surface of the base material; The chemical formula of the matrix material is Na x A y Ni a Cu b Fe c Mn d O 2 , wherein, 0.98≤x≤1.02, 0.001≤y≤0.02, 0.29≤a≤0.31, 0.02≤b≤0.04, 0.31≤c≤0.36, 0.32≤d≤0.36, A includes Ca element and / or Sr element; The coating layer contains B element, and the ratio of the mass of the B element to the mass of the base material is 0.005-0.01:
1.
2. The positive electrode material according to claim 1, It is characterized in that At least one of the following conditions is met: (1) Particle size D of the positive electrode material 50 4~20μm; (2) The specific surface area of the positive electrode material is ≤ 0.5 m 2 / g; (3) The compaction density of the positive electrode material is ≥3.0 g / cm 3 .
3. The method for preparing the positive electrode material according to any one of claims 1 to 2, It is characterized in that The steps include: A copper-nickel-iron-manganese carbonate precursor, a sodium source and an A-containing dopant are mixed and sintered to obtain a matrix material; the A element in the A-containing dopant includes at least one of Ca and Sr, and the ratio y of the molar amount of the A element to the molar amount of the copper-nickel-iron-manganese carbonate precursor is 0.001 to 0.02; The base material and the B-containing coating agent are mixed and then calcined to obtain the positive electrode material; the ratio z of the mass of the B element in the B-containing coating agent to the mass of the base material is 0.005-0.
01.
4. The method for preparing the positive electrode material according to claim 3, It is characterized in that The sum of the theoretical carbon content and the theoretical sulfur content in the positive electrode material satisfies: φ=10×EXP(y) / (|lg(1-z)|×S×D 50 )±200ppm; Wherein, the unit of φ is ppm, ±200 is the error coefficient; S is the specific surface area of the positive electrode material, D 50 is the particle size D of the positive electrode material 50 .
5. The method for preparing the positive electrode material according to claim 4, It is characterized in that The φ=600~1800ppm.
6. The method for preparing the positive electrode material according to claim 3, It is characterized in that At least one of the following conditions is met: (1) The chemical formula of the nickel iron manganese carbonate precursor is Ni m Cu n Fe p Mn q CO 3 , where 0.29≤m≤0.31, 0.02≤n≤0.04, 0.31≤p≤0.36, 0.32≤q≤0.36, and m+n+p+q=1; (2) the sodium source comprises at least one of sodium carbonate, sodium hydroxide and sodium bicarbonate; (3) The A-containing dopant includes at least one of metal oxides, carbonates and hydroxides containing the A element.
7. The method for preparing the positive electrode material according to claim 3, It is characterized in that The B-containing coating agent includes boric acid and / or boron oxide.
8. The method for preparing the positive electrode material according to claim 3, It is characterized in that At least one of the following conditions is met: (1) The sintering temperature is 900-1000° C. and the holding time is 10-30 hours; (2) The sintering atmosphere includes air atmosphere and / or oxygen atmosphere; (3) the calcination is performed at 300 to 800° C. and the holding time is 5 to 15 hours; (4) The calcination atmosphere includes air atmosphere and / or oxygen atmosphere.
9. A positive electrode sheet, It is characterized in that The invention comprises the positive electrode material as claimed in any one of claims 1 to 2, or the positive electrode material prepared by the preparation method of the positive electrode material as claimed in any one of claims 3 to 8.
10. A sodium ion battery, It is characterized in that Comprising the positive electrode sheet as claimed in claim 9.
Citation Information
Cited By
Method for preparing high-capacity and long-cycle sodium electric single-crystal positive electrode material under assistance of carbonate
CN120250133A
A method for preparing high-capacity and long-cycling sodium electric single-crystal cathode materials with the aid of carbonates
CN120250133B
Method for improving stability of sodium ion battery polyanion positive electrode slurry
CN120600810A
